Techlex: A corporate practice to initiate inclusive agri-food value chain development in China - Zhou, Yunyi; Hu, Song; Chen, Kevin Z. (Wageningen Academic Publishers, 2023)
A tradeoff lies between inclusiveness and economic efficiency in meeting the Sustainable Development Goals such as poverty reduction, food security, and climate resilience. Vertical coordination between agribusinesses and farmers, in tandem with corporate social responsibility, has been perceived as an approach to surmount such tradeoff from a micro perspective. In a localized context of developing economies, the vertical coordination with farmers is reducible to a path for agribusinesses towards inclusive local value chain development (LVCD) at the grassroots level. However, few models are documented for agribusiness managers to refer to in practice. This study harnesses the Techlex Group and its pig business as a case, zooming in on the vertical coordination of agribusiness and vulnerable smallholders in lagging rural areas of China. Based on an overview of China’s pig industry and Techlex’s value chain, this study highlights three inclusive models and their alternatives for the LVCD. Though proffered in the Chinese context, those models can enrich the LVCD toolkit and be attuned to fit a different scenario.